Comparison of non-axisymmetric dynamic response of imperfectly bonded buried orthotropic thick and thin cylindrical empty shell due to incident shear wave (SH Wave) / Rakesh Singh Rajput ... [et al.] - Singh Rajput, Rakesh (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2011)
This paper deals with the non-axisymmetric dynamic response of imperfectly bonded buried orthotropic thick and thin empty pipelines subjected to incident shear wave (SH-wave). In the thin shell theory, the effect of shear deformation and rotary inertia is not considered. The pipeline has been modeled as an infinite cylindrical shell imperfectly bonded to surrounding. A thin layer, acting as an imperfect bond, is assumed between the shell and the surrounding medium (soil). The degree of imperfection of the bond is varied by changing the stiffness and the damping parameters of this layer. Although a general formulation has been presented, numerical results are given only for the case of incident SH-waves. When system is excited by incident seismic-wave, there are two types of soil movements take place. One is vertical movement (up and down) of the soil and due to this movement the shear wave (S-V and S-H) is developed on the surface of the pipe and other is horizontal movement (compressive or extend) of the soil due to this the longitudinal wave or pressure wave. In this paper, the results concerning only the shear waves (SH Wave) are presented. The radial displacement of the thin shell first decreases then increases with increasing wave number and for thick shell the radial displacement decreases continuously with increasing wave number.